2016
DOI: 10.1186/s12936-016-1168-y
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of host feeding success by Anopheles farauti

Abstract: BackgroundThe proportion of blood meals that mosquitoes take from a host species is a function of the interplay of extrinsic (abundance and location of potential hosts) and intrinsic (innate preference) factors. A mark-release-recapture experiment addressed whether host preference in a population of Anopheles farauti was uniform or if there were anthropophilic and zoophilic subpopulations. The corresponding fitness associated with selecting different hosts for blood meals was compared by measuring fecundity.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 33 publications
2
12
0
1
Order By: Relevance
“…The original barrier screen collections in Indonesia, the Solomon Islands and Papua New Guinea by Burkot et al [8] used black or green screens without eaves of 70% shading weight, that were checked every 60 min. Russell et al [23] also used green 70% shading weight screens in the Solomon Islands. Moreno et al [22] in Amazonian Peru successfully captured An.…”
Section: Discussionmentioning
confidence: 99%
“…The original barrier screen collections in Indonesia, the Solomon Islands and Papua New Guinea by Burkot et al [8] used black or green screens without eaves of 70% shading weight, that were checked every 60 min. Russell et al [23] also used green 70% shading weight screens in the Solomon Islands. Moreno et al [22] in Amazonian Peru successfully captured An.…”
Section: Discussionmentioning
confidence: 99%
“…While, PNG has experienced prolonged stockouts of antimalarial drugs during that time, it seems unlikely that drug shortages alone will lead to massive resurgence of transmission, if >80% of infections are asymptomatic i.e., remain mostly untreated [11,12]. Studies have also suggested behavioural adaptation of local malaria vectors to LLINs such that biting now occurs earlier [13], however Anopheles farauti, the major vector in PNG exhibited strong preference towards early outdoor biting even before LLINs were introduced [14]. Continued electrification (i.e., with solar-powered lights) allow people to be active much longer into the night than previously, even in remote PNG communities which may enhance human-vector contact further.…”
Section: Introductionmentioning
confidence: 99%
“…Hal ini dikarenakan lokasi penangkapan nyamuk sangat dekat dengan kolam dan aliran paritp a r i t k e c i l ya n g m e r u p a k a n t e m p a t perkembangbiakan dari jenis nyamuk Culex. Kepadatan nyamuk dipengaruhi oleh berbagai faktor diantara adalah dekatnya t e m p a t p e r k e m b a n g b i a k a n d e n g a n 18 pemukiman, ada tidaknya kandang ternak di 20 dekat pemukiman, dan pengaruh suhu dan kelembaban yang cocok untuk perkembangan 21 nyamuk.…”
Section: Analisa Dataunclassified